2018
DOI: 10.1186/s12998-017-0171-x
|View full text |Cite
|
Sign up to set email alerts
|

The schism in chiropractic through the eyes of a 1st year chiropractic student

Abstract: Since its inception, the chiropractic profession has been divided along ideological fault lines. These divisions have led to a profession wide schism, which has limited mainstream acceptance, utilisation, social authority and integration.The authors explore the historical origins of this schism, taking time to consider historical context, religiosity, perpetuating factors, logical fallacies and siege mentality.Evidence is then provided for a way forward, based on the positioning of chiropractors as mainstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Papers in this series have again revealed deeply rooted disagreements within the chiropractic profession about what chiropractic is, and what it should be, as a profession [13,19,20], as well as disagreements and variation in relation to education of chiropractors [14,15] and chiropractic clinical practice [11]. In our opinion, it is ironic that while chiropractic has a strong presence in large parts of the world [3], is taking on increasingly important roles in disability prevention [6,7,17], in the military [5] and in interprofessional care [8] as well as growing research capacity [16], discussions about fundamental values and direction of the profession are unresolved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Papers in this series have again revealed deeply rooted disagreements within the chiropractic profession about what chiropractic is, and what it should be, as a profession [13,19,20], as well as disagreements and variation in relation to education of chiropractors [14,15] and chiropractic clinical practice [11]. In our opinion, it is ironic that while chiropractic has a strong presence in large parts of the world [3], is taking on increasingly important roles in disability prevention [6,7,17], in the military [5] and in interprofessional care [8] as well as growing research capacity [16], discussions about fundamental values and direction of the profession are unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…These authors suggested that it may be time to openly discuss separation or divorce so that the two fractions can pursue a separate future [19]. Strahinjevich and Simpson also targeted the schism between the evidenceoriented and the vitalistic groups in chiropractic as seen through the eyes of a first-year student, and discussed both the historic background for this and possible ways forward [20].…”
Section: Discussion and Debate Papersmentioning
confidence: 99%
“…The technical rationale notes that the subluxation is a correctable and treatable biomechanical lesion via spinal manipulation for the treatment of many health afflictions [ 15 , 24 , 52 ]. The use of anecdotal evidence is used to demonstrate that such a construct exists.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty for chiropractic is that it is essentially two disparate groups held together by a common early history and name. As evidence-based practice continues to expand and strengthen, the groups can be seen to be increasingly divergent and the differences may be irreconcilable [10,224].…”
Section: The Polarizing Effect Of Modernizationmentioning
confidence: 99%